Persepsi Konsumen terhadap Harga, Kualitas, dan Risiko di Resto Tuna House Mega Mas Manado - Yelly A. Walansendow; Steven Y. Kawatak; Ponomban, Teresa; Vincentius W. Rengkung (MAMEN: Jurnal Manajemen, 2022)
Tuna House Mega Mas is an iconic seafood restaurant that is located in the central business district in Manado City, North Sulawesi Province. Due to the COVID-19 pandemic, this restaurant also experiences a decrease in the number of customers. One crucial determinant to obtain new and to retain existing customers is by being perceived positively by customers. This research aimed to ascertain the perception of Tuna House Mega Mas’ customers in terms of price, quality, and risk variables. Each variable was then divided into four indicators accordingly. To find out customers’ perception, a descriptive quantitative method was used by distributing questionnaires to 30 respondents, who were chosen randomly. Each variable and indicator was then compared to the range to find out which category it fell into. The result of this research showed that customers agree that Tuna House Mega Mas’ performance, in terms of price, quality, and risk, was well perceived